2021
DOI: 10.15283/ijsc20088
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone-Marrow vs. Peripheral Blood Mononuclear Cells Therapy for Peripheral Artery Disease in Diabetic Patients

Abstract: Diabetes mellitus (DM) remains one of the most important risk factors for peripheral artery disease (PAD), with approximately 20% of DM patients older than 40 years old are affected with PAD. The current standard management for severe PAD is endovascular intervention with or without surgical bypass. Unfortunately, up to 40% of patients are unable to undergo these revascularization therapies due to excessive surgical risk or adverse vascular side effects. Stem cell therapy has emerged as a novel therapeutic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Stem cells are capable of self-renewing and producing differentiated cells. Based on the degree of differentiation, they can be divided into totipotent, pluripotent, multipotent, oligopotent, or unipotent [ 117 ]. Bone marrow stem cells include various types of progenitor cells: multipotent adult progenitor cells, MSCs, and hematopoietic stem cells [ 118 ].…”
Section: Cell Therapy For Atherosclerotic Cvdsmentioning
confidence: 99%
“…Stem cells are capable of self-renewing and producing differentiated cells. Based on the degree of differentiation, they can be divided into totipotent, pluripotent, multipotent, oligopotent, or unipotent [ 117 ]. Bone marrow stem cells include various types of progenitor cells: multipotent adult progenitor cells, MSCs, and hematopoietic stem cells [ 118 ].…”
Section: Cell Therapy For Atherosclerotic Cvdsmentioning
confidence: 99%
“…Since the discovery that blood cells contribute to postnatal angiogenesis (276), there has been an increasing number of clinical studies to test the efficacy of autologous cell therapies for the treatment of CLTI, ranging from case reports to small series, uncontrolled trials and RCTs reported in numerous meta-analyses (277)(278)(279)(280)(281)(282)(283)(284)(285). The main goal of cell therapy is the induction of therapeutic angiogenesis with the formation of collaterals leading to increased blood flow in the ischemic limb and tissue regeneration in non-healing wounds.…”
Section: Cellular Therapiesmentioning
confidence: 99%
“…V průměru u 40 % pacientů s CLTI však není možné provést PTA ani jiný způsob revaskularizace (9). Tyto případy jsou označované jako "no-option CLTI" a jsou prediktorem nehojících se defektů a neúspěchu chirurgických zákroků (3).…”
Section: "No-option Clti"unclassified
“…Kromě toho BMMNC i PBMMNC mají schopnost sekrece pro-angiogenních faktorů, jako vaskulární endoteliální růstový faktor (VEGF), fibroblastový růstový faktor (bFGF), růstový faktor hepatocytů (HGF) a angiopoein-1. Tímto parakrinním účinkem dále přispívají k podpoře neovaskularizace (9). U MSC byly popsány tři mechanismy neovaskularizace, a to parakrinní aktivita, ke které se radí i jejich imunomodulační účinek, dále přímá diferenciace a mitochondriální transfer.…”
Section: Mechanismus Léčby Kmenovými Buňkamiunclassified